An Initial Evaluation of the Effects of an Exchange Task with Varying Amounts of Exchange Points in Triadic Interactions. - Kazaoka, Kyosuke; Cihon, Traci M. (Behavior & Social Issues, 2025)
The purpose of this sequence of studies was to identify and analyze the patterns of interactions among participants in a basic experimental setting. Two studies were conducted in the context of a three-person exchange task. Participants, in triads, were asked to choose from an array of three task choices that produced points for themselves (independent task) or gave points to one of the other participants (giving tasks). A multiple baseline design was used to increase the number of points that corresponded to the giving tasks across participants in an attempt to manipulate the "internal dynamics" of participants' interactions. The results showed that 14 of 18 participants allocated more of their choices to the giving tasks over the independent tasks, which resulted in some participants reinforcing each other's choice allocations. The current studies, however, did not demonstrate clear control by programmed experimental conditions on participants' choices, potentially due to contingencies that emerged as a function of the participants' choices. The results are discussed with respect to their potential to extend the literature on social behavior and the metacontingency and their relevance to social issues. Future research strategies to increase experimental control by experimental conditions in triadic exchange tasks are also discussed.